Site-specific cross-linking of proteins to DNA via a new bioorthogonal approach employing oxime ligation. Issue 49 (31st May 2018) - Pujari, Suresh S.; Zhang, Yi; Ji, Shaofei; Distefano, Mark D.; Tretyakova, Natalia Y.
Abstract : Model site-specific DNA–protein cross-link formation by bioorthogonal oxime ligation. Abstract : DNA–protein cross-links (DPCs) are super-bulky DNA adducts induced by common chemotherapeutic agents, reactive oxygen species, and aldehydes, and also formed endogenously as part of epigenetic regulation. Despite their presence in most cells and tissues, the biological effects of DPCs are poorly understood due to the difficulty of constructing site-specific DNA–protein conjugates. In the present work, a new approach of conjugating proteins to DNA using oxime ligation was used to generate model DPCs structurally analogous to lesions formed in cells. In our approach, proteins and peptides containing an unnatural oxy-Lys amino acid were cross-linked to DNA strands functionalized with 5-formyl-dC or 7-(2-oxoethyl)-7-deaza-dG residues using oxime ligation. The conjugation reaction was site-specific with respect to both protein and DNA, provided excellent reaction yields, and formed stable DPCs amenable to biological evaluation.